Optimization, Modeling and Simulation of Microclimate and Eenergy Management of the Greenhouse by Modeling the Associated Heating and Cooling Systems and Implemented by a Fuzzy Logic Controller using Artificial Intelligence - Didi, Faouzi; Bibi-Triki, Nacereddine; Mohamed, Bentchikou; Abène, Abderrahmane (Informatica, 2017)
Agricultural greenhouse aims to create a favorable microclimate to the requirements of growth and development of culture, from the surrounding weather conditions, produce according to the cropping calendars fruits, vegetables and flower species out of season and widely available along the year. It is defined by its structural and functional architecture, the quality thermal, mechanical and optical of its wall, with its sealing level and the technical and technological accompanying. The greenhouse is a very confined environment, where multiple components are exchanged between key stakeholders and them factors are light, temperature and relative humidity. This state of thermal evolution is the level sealing of the cover of its physical characteristics to be transparent to solar, absorbent and reflective of infrared radiation emitted by the enclosure where the solar radiation trapping effect otherwise called "greenhouse effect" and its technical and technological means of air that accompany. New climate driving techniques have emerged, including the use of control devices from the classic to the use of artificial intelligence such as neural networks and / or fuzzy logic, etc... As a result, the greenhouse growers prefer these new technologies while optimizing the investment in the field to effectively meet the supply and demand of these fresh products cheaply and widely available throughout the year. In north Africa, greenhouse cultivation is undergoing significant development. To meet an increasingly competitive market and conditioned by increasingly stringent quality standards, "Greenhouse" production systems (heating and air-conditioning systems) Become considerably sophisticated and then disproportionately expensive. That is why locks who want to remain competitive must optimize their investment by controlling production conditions. The aim of our work is to model heating and air conditioning systems whose goal of heating and cooling the air inside our model and implemented in our application of climate control are due to the fuzzy logic that Has the role of optimizing the cost of the energy supplied using MATLAB software.